THE EFFECTIVENESS OF EDUCATIONAL GAMES IN MATH LEARNING IN ELEMENTARY SCHOOL - Dyah Anungrat Herzamzam (Universitas Sebelas Maret, 2018)
The purpose of this research is to know the effectiveness of: (1) android-based educational games and (2) without the games in learning mathematics.This type of research is experimental with Pretest-Posttest design Randomized Control Group Design. In the process of experimentation conducted observations on two groups of learning i.e. experimental group one which was given treatment with android-based educational games in math, learning and a control group with no game. The population of the research was all learners class II SD PB Sudirman Jakarta with samples of learners classes IIA, IIB, and IIC. Research instrument was a matter of addition and subtraction tests that have been tested with Alpha 0.826. Data analysis techniques using Anava followed by Scheffe test. The results showed that: (1) there is a significant difference in effectiveness between learning mathematics using android-based educational games and without a game in learning addition and subtraction class II SD PB Sudirman Jakarta Timur ( FH = 6.211 > Ft (0.05) = 3.02); (2) there is a significant difference in the effectiveness of media math learning using android-based educational games and learning in games without fractions, (sig (p) = 0.005 < 0.05); This shows that the educational learning games mathematics better and effective than without games.